De « la voix de la France » à « l’État annonceur » - Caroline Ollivier-Yaniv (Communication)
Today, communication is considered to be evident and necessary in French governmental institutions. However, the rendering systematic of the address to citizens by the executive power does not result solely from institutional changes, from the eternal project of modernisation of the administration, or even from the development of political communication in general. The institutionalisation of French governmental communication can in fact be understood as the contemporary realisation — sophistication because it is democratically correct (in contrast with propaganda) — of the tradition of massive intervention of the French State in matters of information, in other words, of the Dispositif of State information.